2017
DOI: 10.1038/s41598-017-07427-x
|View full text |Cite
|
Sign up to set email alerts
|

Earliest expansion of animal husbandry beyond the Mediterranean zone in the sixth millennium BC

Abstract: Since their domestication in the Mediterranean zone of Southwest Asia in the eighth millennium BC, sheep, goats, pigs and cattle have been remarkably successful in colonizing a broad variety of environments. The initial steps in this process can be traced back to the dispersal of farming groups into the interior of the Balkans in the early sixth millennium BC, who were the first to introduce Mediterranean livestock beyond its natural climatic range. Here, we combine analysis of biomolecular and isotopic compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 41 publications
7
72
0
1
Order By: Relevance
“…Studies have shown that cattle prefer water-rich environments (Gander et al, 2003), whereas caprines can survive in areas of aridity like the Mediterranean and the Balkans (Boyazoglu and Morand-Fehr, 2001). Milk exploitation was a component of early Neolithic farming across most regions of Europe (Helmer and Vigne, 2004;Helmer et al, 2007;Vigne and Helmer, 2007;Evershed et al, 2008;Debono Spiteri et al, 2016;Ethier et al, 2017) with caprines and cattle being the main milk producers along the Mediterranean and in Central Europe, respectively. There is little evidence for dairying in areas of the initial expansion of Neolithic cultures in Greece and South-East Europe, although by the time Neolithic culture have spread to the Cycladic islands caprines appear to be managed for milk (Debono Spiteri et al, 2016).…”
Section: The Evolution Of Dairying In Europementioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that cattle prefer water-rich environments (Gander et al, 2003), whereas caprines can survive in areas of aridity like the Mediterranean and the Balkans (Boyazoglu and Morand-Fehr, 2001). Milk exploitation was a component of early Neolithic farming across most regions of Europe (Helmer and Vigne, 2004;Helmer et al, 2007;Vigne and Helmer, 2007;Evershed et al, 2008;Debono Spiteri et al, 2016;Ethier et al, 2017) with caprines and cattle being the main milk producers along the Mediterranean and in Central Europe, respectively. There is little evidence for dairying in areas of the initial expansion of Neolithic cultures in Greece and South-East Europe, although by the time Neolithic culture have spread to the Cycladic islands caprines appear to be managed for milk (Debono Spiteri et al, 2016).…”
Section: The Evolution Of Dairying In Europementioning
confidence: 99%
“…Mediterranean livestock were introduced beyond their natural climatic range by farming groups dispersing into the interior of the Balkans by 7.6 kyBP. Climate-driven selective pressures led to a better adaptation of the livestock to their new environment (Ethier et al, 2017).…”
Section: The Evolution Of Dairying In Europementioning
confidence: 99%
See 1 more Smart Citation
“…To se posebno odnosi na istraživanja laktolipida (na primer Craig et al 2005;Copley et al 2005aCopley et al , 2005bCopley et al , 2005c, koja su pokazala da je mleko korišćeno u ishrani još od rane praistorije, ili širenja zajednica s pastoralnom ekonomijom u različitim ekološkim nišama u vreme neolitske revolucije (Ethier et al 2017). Iako su nesumnjivo važna, fokus ovih istraživanja je, međutim, veoma udaljen od keramičkih studija: u njima je keramika samo izvor podataka, ali ne i predmet istraživanja.…”
Section: J V 692unclassified
“…As Neolithic agriculture spread from its centre of independent origins in the Near East, its pathway bifurcated in the eastern Mediterranean, with one expansion north through Eastern Europe and another westward along the European shores of the Mediterranean (McClure, ; Rowley‐Conwy, ). The westward expansion maintained the pattern of predominantly caprine husbandry seen in the eastern Mediterranean, whereas the northward expansion gave rise to an increasing frequency of cattle (Manning et al, ), probably as an adaptation to continental life north of the Alps (Ethier et al, ; McClure, ). Despite this adaptive change to temperate ecosystems (Ivanova, De Cupere, Ethier, & Marinova, ) in favour of cattle (Manning et al, ), caprines ( Ovis sp./ Capra sp.)…”
Section: Introductionmentioning
confidence: 97%